Digital-skills of building economists in the era of VUCA and BANI-WORLD - Tsyfra, T.; Moholivets А.; Vershigora , D. (Ways to Improve Construction Efficiency, 2022)
This article is devoted to the formation and use of digital-skills by construction economists at the turn of the era of VUCA-world and BANI-world concepts. Especially given the current realities of globalization of socio-economic institutions and institutions, challenges related to climate change, pandemics, military conflicts and cataclysms, digital skills will replace the "soft" skills needed by construction economists, both in training and continuing education. for life. The treacherous, inhuman aggression of the Russian Federation has caused large-scale destruction of housing, industrial buildings and infrastructure. Restoration of damaged and lost objects is associated with considerable costs, the amount of which is currently almost impossible to estimate. Despite the unprecedented steps of the Government of Ukraine, first of all, the simplification of procedures for the import of construction materials, to avoid the problem of rising construction costs, unfortunately, will not succeed. First of all, in order to rebuild Ukraine as soon as possible, there will be an increase in demand for construction materials, products and kits in most international markets. At the same time, world prices will definitely grow. In turn, the cost of construction and the need to increase investment will increase. This problem will be most acute for all participants in housing construction, as in the post-war conditions such projects will be deprived of a commercial component. According to the Network Readiness Index, Ukraine is relatively well developed in such areas as technology, human capital, economy, living standards and contribution to the UN Sustainable Development Goals. The harmonious development of digital skills of construction economists at the turn of the VUCA and BANI epochs on the basis of market organizational and economic mechanisms and public e-government will enable the sectors and economies of construction companies and construction economists to make a digital leap. BANI is a way to better understand the current state of the world and somehow respond to it. Some of the changes in society, the environment and technology are familiar to us - they are stressful, but we have encountered them before. But so many changes are taking place now that are unfamiliar, incomprehensible and disorienting. They increase the stress we feel and increase it. As in the acronym VUCA, each letter BANI has a special meaning that affects the concept. The paper simulates, taking into account the BANI concept, using a factor-criterion qualimetric model to assess the level of professional motivation of the Kovalska Group on the example of construction economists and communicative interaction on the example of the personnel department during martial law in Ukraine. The use of these models will help eliminate bias in the evaluation process, help manage motivation, inform employees and managers about development reserves (growth), increase the level of positive communicative interaction with the environment, ie purposefully manage productive activities with digital-skills in VUCA and BANI-world.